'If he dies with the papers of his brother, his brother will be considered dead'. Moral understandings of health professionals about the use of deception to overcome restrictions in access to healthcare. (June 2020) - Lafaut, Dirk
Although scholars in bioethics usually consider the exclusion of migrants from basic healthcare as unjust, it remains unclear how health professionals should ethically deal with policies restricting access to healthcare for undocumented migrants. Debates on offering less than the most beneficial healthcare have been limited to contributions on ethical bedside rationing. This article draws on semi-structured in-depth interviews that explore health professional's acceptance, as well as their willingness to resort to the use of deception to secure third-party payer approval for undocumented migrants. The results show that health professionals (1) are sceptical about both the possibility and desirability of verifying whether a patient's declarations are deceitful in the setting of a consultation, but (2) are reluctant to use deception themselves to circumvent government policies restricting access to healthcare for undocumented migrants. We discuss how this approach of 'relative impartiality' threatens professional autonomy and conclude that professional associations should play a much more important role in supporting health professionals in relation to healthcare institutions and governments when their members are confronted with specific rationing practices forcing them to provide suboptimal healthcare.